2019
DOI: 10.3390/su11041046
|View full text |Cite
|
Sign up to set email alerts
|

Co-CEOs and Asymmetric Cost Behavior

Abstract: This study investigates the effect of co-CEO structure on asymmetric cost behavior. A firm’s cost behavior reflects managers’ decision making about resources, which can be influenced by various factors. One of them relates to a manager’s decision to inefficiently reallocate their company’s resources when sales decline in pursuit of their incentives for empire-building and disincentives for downsizing. These inefficient resource allocations may result in asymmetric cost behavior, and ultimately be harmful to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The managers' knowledge of the direction and magnitude of sales changes in the past affects their decisions in managing their resources, thus having an impact on cost stickiness (Anderson et al, 2013;Brüggen & Oliver, 2014;Ciftci & Zoubi, 2019;Özkaya, 2020;Sepasi & Has sani, 2015). Likewise with the relationship between the assets and workers' intensity and costs (Anderson et al, 2003;Bradbury & Scott, 2018;Bugeja et al, 2015;Chae & Ryu, 2016;Cheung et al, 2018;Gorodnichenko & Weber, 2016;Kama & Weiss, 2013;Kitching et al, 2016;Lee et al, 2019;Mohammadi & Taherkhani, 2017;Namitha & Shijin, 2016;Prabowo et al, 2018;Venieris et al, 2015;Via & Perego, 2014;Xu & Sim, 2017;Zanel la et al, 2015). Improved economic growth tends to make managers more optimistic (Banker et al, 2013;Bu et al, 2015;Fitzgerald & Haller, 2013;Yang & Zhang, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The managers' knowledge of the direction and magnitude of sales changes in the past affects their decisions in managing their resources, thus having an impact on cost stickiness (Anderson et al, 2013;Brüggen & Oliver, 2014;Ciftci & Zoubi, 2019;Özkaya, 2020;Sepasi & Has sani, 2015). Likewise with the relationship between the assets and workers' intensity and costs (Anderson et al, 2003;Bradbury & Scott, 2018;Bugeja et al, 2015;Chae & Ryu, 2016;Cheung et al, 2018;Gorodnichenko & Weber, 2016;Kama & Weiss, 2013;Kitching et al, 2016;Lee et al, 2019;Mohammadi & Taherkhani, 2017;Namitha & Shijin, 2016;Prabowo et al, 2018;Venieris et al, 2015;Via & Perego, 2014;Xu & Sim, 2017;Zanel la et al, 2015). Improved economic growth tends to make managers more optimistic (Banker et al, 2013;Bu et al, 2015;Fitzgerald & Haller, 2013;Yang & Zhang, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These articles have not been used because they discuss the effects of cost stickiness on, for example, the forecasting of earnings (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). Be cause our focus is the managers' behaviour, we have dropped 15 articles that discuss, for example, the effect of an auditor's choice, ac counting policies, changes in office address, CEO structure, and changes in the research sample on cost stickiness (Chae & Chung, 2015;Chae & Ryu, 2016;Chung et al, 2019;Ibrahim, 2018;Lee et al, 2019;Loy & Hartli eb, 2018;Shust & Weiss, 2014;Xue & Hong, 2016;Yang, 2015). The final number of re search articles in the literature we used in this study was 56.…”
Section: Methodsmentioning
confidence: 99%
“…They can manipulate resources in an attempt to increase earnings or decrease earnings, in order to benefit their own agendas. For example, when "empire building" CEOs fail to cutback resources as sales decrease is an example of management wanting to grow the firm to a greater size rather than the optimal one, Lee, Park, Hyeon (2019). Additionally, you have situations where management seeks to manipulate expenses to increase earnings.…”
Section: Ethical Issues and Compensationmentioning
confidence: 99%
“…They found that cost stickiness was least likely to be found in a co-CEO structure then a single CEO. The dual CEO roles served as "an alternative internal corporate governance tool for mitigating" decisions that would result in sticky costs Lee, et al (2019). In a study by Xu and Hong (2016) they found that good corporate governance has a negative impact on cost stickiness.…”
Section: Ethical Issues and Compensationmentioning
confidence: 99%
“…A large part of the agency problem literature focuses on determining the optimal balance between risk-taking and risk avoidance and the instruments to achieve that balance [3], with corporate governance [4,5], or company audit [6]. Those instruments can include management motivation agreements.…”
Section: Introductionmentioning
confidence: 99%